Lokalizace telomerických elementů u Drosophila melanogaster - Pavlechová, Iveta (Jihočeská univerzita, 2016)
Telomeres are nucleoprotein structures at the ends of eukaryotic chromosomes, performing several vital functions. One of the functions is the compensation of telomeric loss resulting from incomplete replication. Drosophila telomeres consist of an array of telomeric retroelements HeT-A, TART and TAHRE, that compensate for the telomeric losses by their transposition, targeted to chromosome ends. This study shows that targeting of each of the elements is not strictly specific to any of the telomeres as each telomeric element was observed in all telomeres. Using Drosophila lines possesing a different telomere length it has been shown that long telomere length results in more efficient telomere clustering.
Localisation of telomeric elements in Drosophila melanogaster